Modern trends in labor market transformation in post-sovietcountries – causes and challenges - Sreseli, Lali (Dnipro University of Technology, 2025)
The transformation of the country&39’s economy significantly depends on minimizing unemployment, optimal use of labor resources, and the formation of a modern civilized labor market. The article discusses the current trends in employment of the population in the post-Soviet countries during the transition period from a planned economy to a market economy, the objective and subjective causes of structural unemployment, and the impact of regional characteristics of the labor market on the quality of employment. Трансформація економіки країни значною мірою залежить від мінімізації безробіття, оптимального використання трудових ресурсів, формування сучасного цивілізованого ринку праці. У статті розглядаються сучасні тенденції зайнятості населення пострадянських країн у перехідний період від планової до ринкової економіки, об’єктивні та суб’єктивні причини структурного безробіття, вплив регіональних особливостей ринку праціна якість зайнятості.
Сучасні тенденції трансформації ринку праці в пострадянських країнах – причини та проблеми
Keywords: labor market; employment; unemployment; migration; ринок праці; зайнятість; безробіття; міграція.